2017
DOI: 10.1016/j.seizure.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel in the general population and in people with intellectual disability: Differing responses

Abstract: PER seems safe in PWE with ID. It is better tolerated by PWE with Moderate to profound ID than PWE with higher functioning. Caution is advised when history of mental health problems is present. The standardised approach of the Ep-ID register UK used confirms that responses to AEDs by different ID groups vary between themselves and General population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
(36 reference statements)
1
28
1
Order By: Relevance
“…Perampanel doses of 6‐8 mg are most common in studies of routine clinical use, and slightly lower doses may be effective in some populations such as older people and those with intellectual disability. For example, people with epilepsy and profound intellectual disability were maintained on a lower perampanel dose (median 4 mg) than people with mild or no intellectual disability (median 6 mg) . Our subpopulation of people aged ≥65 used a lower median dose (6 mg) than the overall population (8 mg).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Perampanel doses of 6‐8 mg are most common in studies of routine clinical use, and slightly lower doses may be effective in some populations such as older people and those with intellectual disability. For example, people with epilepsy and profound intellectual disability were maintained on a lower perampanel dose (median 4 mg) than people with mild or no intellectual disability (median 6 mg) . Our subpopulation of people aged ≥65 used a lower median dose (6 mg) than the overall population (8 mg).…”
Section: Discussionmentioning
confidence: 82%
“…Investigators who had already gathered data were identified and invited to participate, with the aim of obtaining a full analysis set (FAS) of at least 2000 people. Some centers included here had previously published results . Appropriate ethics committee approvals and informed consent were obtained by centers for the original data acquisition and for incorporating data into this analysis, as required.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Published real‐world data with perampanel is mainly from patients with focal seizures, or small case series in specific seizure types, like progressive myoclonic epilepsies or drug‐resistant myoclonic seizures . The phase III perampanel trial in IGE included few patients with myoclonic or absence seizures, so the effect of perampanel on these seizure types could not be determined .…”
Section: Introductionmentioning
confidence: 99%